A160 IBD PATIENTS' ACCESS TO TELEPHONE / EMAIL SERVICE PROVIDED BY IBD NURSES IN CANADA. (1st March 2018) - Chauhan, U; Nistor, I; Currie, B; Nicholl, J; McCaw, W; Watson, M; Westin, L; Fernandes, A; Norton, C
Abstract: Background: IBD is characterized by intermittent exacerbations of disease, known as 'flares', with activity free periods of 'remission'. The course of disease is unpredictable and it has a substantial negative impact on patients' quality of life and healthcare resources. The care of IBD patients extends beyond routine medical provider office visits as the disease activity is unpredictable and it does not coincide with the scheduled appointments. Nurses play an integral part in ensuring access to care during and between office visits. Aims: The primary objective of this study was to examine the utilization of IBD nursing telephone/email service provided to IBD patients during a 14 day period in Canada. Methods: Using a mixed method approach, data was collected by CANIBD Nurses conducting an audit of telephone / email services provided by nurses working with IBD patients over a 2-weeks period. The nurses' interactions with IBD patients were compared using paired and independent t-tests. Results: 84 IBD nurses across Canada were invited to participate in the study. 21 nurses participated in the study, including 4 research nurses, 7 adult and 2 pediatric RNs, 2 Clinical Nurse Specialists, 6 Nurse Practitioners (4 adult and 2 pediatric) with good representation from across the country. 431 encounters were reported: 78 (14%) via email, 327 (57%) via telephone and 26 (5%) telephone conversation following email interaction. The reasons for the telephone/email contact were divided into 9 themes: disease flare, other GI symptoms, medication related concerns, follow up with investigation results, scheduling appointments, questions related to insurance coverage, psychosocial concerns, financial concerns and other. Based on their interaction with the IBD patients, IBD nurse(s) were able to provide nurse managed interventions 343(60%), schedule an appointment in the IBD Clinic 112 (20%), consult the primary healthcare practitioner 109 (19%), consult an allied health practitioner such a dietician or ostomy nurse 13 (2%), instructed the patient to go to the Emergency Department 10 (2%), contact a patient support program 48 (8%), schedule a follow up telephone call to reassess 66 (12%), adjust medications 6 (1%) and other 111 (20%). Conclusions: A few IBD nurses in Canada offer telephone/email access to care for IBD patients. Although 84 IBD nurses were invited to participate in this outpatient IBD nursing practice audit, only 21 completed the survey. IBD nurses are a critical point of contact for patients and our study identified and compared common reason for call in the adult and pediatric settings. Nurses were able to manage the "reason for call" 60% of the time. Further research would be valuable to explore the impact IBD nurses have on the wellbeing of patients with IBD and their healthcare utilization. Funding Agencies: None